Microstructural evolution of AZ61-10 at.%Ti composite powders during mechanical milling. (15th August 2016) - Yu, Huan; Sun, Yu; Hu, Lianxi; Zhou, Haiping; Wan, Zhipeng
Abstract: The nanocrystalline AZ61 containing 10 at.%Ti composite powders were synthesized by mechanical milling. The results indicate that mechanical milling is available to prepare AZ61-10 at.%Ti composite powders with nanocrystalline Mg matrix, fine dispersed Ti particles and supersaturated solid solutions of Al and Ti in Mg matrix. The microstructure and morphology evolution of magnesium matrix and Ti particles were observed by SEM and TEM. Meanwhile the solid solubility and grain size evolution of Mg matrix were calculated by XRD, with the corresponding mechanism being analysed. Specifically, the Mg grain and the Ti particles were refined with the increasing milling time. The Mg grain was refined to approximately 58.2 nm and the Ti particle size was reduced to around 558 nm after 110 h mechanical milling. From XRD results of the as-milled powders, the supersaturated solid solution of Ti and Al in Mg matrix were detected. Generally, the Al might be completely dissolved into the Mg matrix after 110 h mechanical milling. Correspondingly, the solid solubility of Ti in Mg matrix was estimated to be 3.18 at.%. The micro-hardness of as-milled composite powders increased with the increasing milling time. The micro-hardness could reach 120.42 HV being 2.1-fold the micro-hardness of raw AZ61 alloy. Graphical abstract: Highlights: The grain of as-cast AZ61 turnings was refined to nanocrystalline by mechanical milling. The solid solubility extension of Ti in Mg matrix was achieved. Large Ti particles with average size of 45 μm were smashed to approximately 558 nm. Submicron-size Ti particles were dispersed uniformly in Mg matrix.